Dielectric Properties of Polyimides Being Modified with Fullerene - J. Suboch; A. Valozhyn (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains results of research in respect of dielectric properties of aromatic ПМ-1 and Upilex-type polyimides being modified with various quantity (0.1-2.0 % weight) of C60 fullerene. It is ascertained that temperature is influencing on time constants of p-relaxation of investigated materials.